Attentional Conflict Moderates the Association Between Anxiety and Emotional Eating Behavior: An ERP Study - Denke, Greg; Rawls, Eric; Lamm, Connie (Frontiers in Human Neuroscience, 2018)
Emotional eating is an attempt to avoid, control, or cope with negative emotions through eating a large amount of calorie dense sweet and/or high fat foods. Several factors, including various attentional mechanisms, negative affect, and stress, impact emotional eating behavior. For example, attentional narrowing on negative events may increase attentional stickiness and thereby prevent the processing of more peripheral events, such as eating behavior. This study contributes to the extant literature by examining the neural correlates underlying the attentional conflict between processing negative events and regulating behavior within a task that emulates how negative life experiences might contribute to unrestrained eating behavior. We explore this question within a normative sample that varies in their self-reported anxiety symptoms. Dense-array EEG was collected while participants played the attentional blink game—a task in which excessive attentional resource allocated to one event (e.g., negative picture) interferes with the adequate attentional processing of a second event that requires action. To assess the attentional conflict, we measured N2 activation, an event-related potential (ERPs; averaged EEG) associated with conflict processing. Results revealed that N2 activation moderates the association between anxiety and emotional-eating behavior. Thus, increased anxiety combined with more negative N2 activation can contribute to emotional-eating behavior. These results are discussed in the context of ineffective conflict processing contributing to poor emotion regulation.